TUPAI ENDEMIK DI KALIMANTAN Endemic Plant Shrew in Kalimantan: Satrio Wibowo - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTA study have done by scientists on plant shrews in Kalimantan, as result indicated there were five endemic plantshrews, Dendrogale melanura, Tupaia dorsalis, T. montana, T. picta dan T. splendidula. They appoint to endemicespecially Kalimantan were estimated consequence formed barrier on the era broken Kalimantan from motherterrestrial Asia on Pleocene epoc (estimated two million years ago). Untill now there have been opposite proceedson the plant shrews ancestor, many scientists said they were inherited from Primate order and the others said theywere insectivores, but the recent taxonomy to classify into Scandentia order. The shrews have insectivore andfrugivore characters. Whereas the Bornean nonendemic shrews among other things Tupaia glis, T. minor andPtilicercus lowi, because theyhave been found in outside of Kalimantan area.Keywords: Tree shrews, Endemic, Kalimantan